2014
DOI: 10.1007/s11606-014-3104-6
|View full text |Cite
|
Sign up to set email alerts
|

Patients Report Better Satisfaction with Part-Time Primary Care Physicians, Despite Less Continuity of Care and Access

Abstract: BACKGROUND:The growing number of primary care physicians (PCPs) reducing their clinical work hours has raised concerns about meeting the future demand for services and fulfilling the continuity and access mandates for patient-centered care. However, the patient's experience of care with part-time physicians is relatively unknown, and may be mediated by continuity and access to care outcomes. OBJECTIVE: We aimed to examine the relationships between a physicians' clinical full-time equivalent (FTE), continuity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 42 publications
0
40
0
1
Order By: Relevance
“…4 Perhaps patient satisfaction is more strongly influenced by the negative impact of burnout than the positive impact of continuity.…”
Section: Why Physician Work Hours Are Decreasingmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Perhaps patient satisfaction is more strongly influenced by the negative impact of burnout than the positive impact of continuity.…”
Section: Why Physician Work Hours Are Decreasingmentioning
confidence: 99%
“…10 Although these physicians may have worse continuity and access, they appear to provide a better patient experience. 4 Perhaps patient satisfaction is more strongly influenced by the negative impact of burnout than the positive impact of continuity.…”
Section: Why Physician Work Hours Are Decreasingmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect this has something to do with the nature of the encounters: in internal medicine, patients select their providers and would switch if they did not like the provider; however, this may be different in the typically episodic nature of procedural specialties. While one prior finding did not find an association between specialty and patient experience scores, the study only included internal medicine and family medicine physicians 5. An additional study with broader ranges of specialties did find a difference between specialties 7.…”
Section: Discussionmentioning
confidence: 80%
“…The literature evaluating the link between physician factors and patient experience scores in the clinic setting is very limited but is concordant with our findings. A study of patient experience scores in a single multispecialty group practice of mostly primary care physicians found no association between gender and scores 5. Another study of exclusively rheumatology patients also found no association between scores and physician gender or training level 6.…”
Section: Discussionmentioning
confidence: 97%